Związki hiponimiczne wyrazów w systemie leksykalnym języka rosyjskiego (na materiale czasowników) - Kotcowa, Elena (Studia Rossica Posnaniensia, 2010)
My presentation deals with different approaches to the understanding of the hyponymical relations in the Russian language, the difference between these relations in the sphere of noun and in the sphere of verb, criteria of the verbal hyponymy and its place in the semantical classification of verbs from the point of view of the cognitive approach.